A STRAIGHTFORWARD SYNTHESIS OF NOVEL 1,3,5-TRIAZINE-BASED MACROCYCLIC SCAFFOLDS - CRIŞAN, Cosmin V.; HĂDADE, Niculina D.; GROSU, Ion; CRIŞAN, Andreea P.; TEREC, Anamaria (Studia Universitatis Babeș-Bolyai Chemia, 2020)
The synthesis and structural investigation of a series of three macrocycles bearing 2,4,6-tris(p-phenylene)-1,3,5-triazine central units and oligoethyleneoxide bridges are reported. The approach implied the synthesis of non-symmetrical 1,3,5-triazines obtained via a cross-cyclotrimerization reaction, followed by a direct macrocyclization with the corresponding ditosylated oligoethyleneglycols. The obtained non-symmetrically C-substituted 1,3,5-triazines macrocycles were characterized by NMR spectroscopy and High-Resolution Mass Spectrometry (HRMS).